Karakteristik Eksekutif, Intensitas Modal & Tax Avoidance - Edy Suprianto; Ummul Aqida (Jurnal Akuntansi Indonesia, 2020)
This study aims to examine and analyze the influence of the executive characteristics on tax avoidance with capital intensity as an intervening variable in that LQ45 companies listed in Indonesia Stock Exchange Year 2016-2018. This study uses a quantitative approach. The study includes 28 companies LQ45 listed in Indonesia Stock Exchange within the period 2016-2018. The results showed that the executive characteristics does not affect of tax avoidance, the capital intensity of the positive effect on tax avoidance, executive characteristics positive effect on capital intensity and executives characteristics positive effect on tax avoidance through the capital intensity as an intervening variable.Keywords: Tax Avoidance, Executive characteristics, Capital intensity.